Design of UAV and ground station antenas for communications link budget improvement - Costa, Andreia (2018)
This paper presents the design and implementation of two antennas aiming the improvement of the link budget between an Unmanned Aerial Vehicle (UAV) and the ground station. The performance of the antennas is simulated using CST software tool and the simulation results are found to be in good agreement with the measurements. The UAV antenna presents 6 dBi of gain with an omni-directional coverage. The ground station antenna is a directional antenna based on a stacked configuration allowing an increase of the bandwidth while achieving a gain of 13.5 dBi. Both antennas operate at 1.335 GHz and a range of 50 Km is predicted when included in the communication system.